Revision of the Afrotropical Xorides Latréille, 1809 (Hymenoptera, Ichneumonidae, Xoridinae), with description of three new species - Varga, Oleksandr (Zootaxa, 2019)
Twelve species of Xorides Latréille, 1809 are recorded from the Afrotropical region, three species described as new: X. nigrithorax sp. n., X. rufofacialis sp. n., and X. simoni sp. n. The males of X. maculiceps (Cameron, 1906) and X. praestans (Tosquinet, 1896) are described for the first time. The following synonymies are established: X. maculiceps (Cameron, 1906) = X. maculatus (Benoit, 1952) syn. n.; X. aciculatus (Benoit, 1952) = X. similis (Benoit, 1952) syn. n. Xorides serratitibia (Enderlein, 1914) is placed as incertae sedis. A key to the Afrotropical Xorides species is provided.